Development of an internet of things based smart cold storage with inventory monitoring system - Angappan, Suganya; Nataraj, Aarthi; Krishnan, Loganathan Navaneetha; Palanisamy, Anbarasu (Institute of Advanced Engineering and Science, 2025)
Consuming fresh drupes, vegetables can help lower a chance of developing several chronic diseases. Unfortunately, the post-harvest life cycle's storage stage is where fruits and vegetables (FVs) lose the most of all the food that is produced annually. A failure to recognize important ambient environmental conditions when using cold storage seems to be the main causes of this elevated loss rate. The current monitoring systems for cold storage are only able to measure warmth and moistness and ignoring further crucial acceptable surrounding factors of radiance and gas quantity. Serious matter gets handled in order to lower the system’s harm degree. The real time intelligent monitoring and notification system (RT-IMNS) for icy container is described briefly in the paper. It employs a device management platform (IoT)-enabled technique to continuously monitor hotness, comparative moisture, brightness, fume quantity and alert staff when dangerous thresholds are reached.